Socio-Economic Contribution of Selected Non-Timber Forest Products to Rural Livelihoods of Ipetu Ikeji Forest Reserve, Osun State - Ayetan, Yetunde Balikis; Odeyale, Olajumoke; Fadipe, Oluwasegun Babatunde; Onisile, Adebayo O. (FUDMA Journal of Sciences, 2026)
Forest is a land area covered with trees which serves as habitant for flora and faunas. It is a vital component of ecosystem that provides a wide range of goods and services for support, human well-being and livelihoods. This study examined the socio-economic contribution of selected Non-Timber Forest Products (NTFPs) to the rural livelihoods of communities surrounding Ipetu-Ikeji Forest Reserve in Osun State, Nigeria. It specifically identified the major NTFPs utilized in the area and assessed their contributions to household welfare and livelihood sustainability. A two-stage sampling technique was adopted in selecting respondents from the study area. A total of 125 questionnaires were administered, and 99 were retrieved and analyzed using descriptive statistics such as frequency and percentage. The findings revealed that the majority of respondents were female (77.8%), married (70.7%), and within the economically active age range of 31–40 years (65.7%). Bitter kola (Garcinia kola) was identified as the most common and most utilized NTFP. The study further showed that NTFPs contribute significantly to household livelihoods through income generation, food supply, medicinal uses, and payment of school fees. Most respondents (81.8%) considered NTFPs very important to their livelihoods, while 80.8% affirmed that income from NTFPs improved household welfare. The study concluded that NTFPs play a vital role in supporting rural livelihoods and reducing poverty among forest-dependent households around Ipetu-Ikeji Forest Reserve. The study therefore recommends sustainable forest management practices, improved access to training, and support for cooperative societies to enhance the long-term benefits of NTFPs to rural communities.